2013
DOI: 10.1073/pnas.1310658110
|View full text |Cite
|
Sign up to set email alerts
|

RVX-208, an inhibitor of BET transcriptional regulators with selectivity for the second bromodomain

Abstract: Bromodomains have emerged as attractive candidates for the development of inhibitors targeting gene transcription. Inhibitors of the bromo and extraterminal (BET) family recently showed promising activity in diverse disease models. However, the pleiotropic nature of BET proteins regulating tissue-specific transcription has raised safety concerns and suggested that attempts should be made for domain-specific targeting. Here, we report that RVX-208, a compound currently in phase II clinical trials, is a BET brom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
406
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 412 publications
(435 citation statements)
references
References 45 publications
20
406
0
4
Order By: Relevance
“…RVX2135 belongs to a different scaffold, which has a higher selectivity for BD2 over BD1 of the BET proteins. This property is shared by RVX-208, a BET inhibitor with the same scaffold that is undergoing clinical trial for arteriosclerosis (13)(14)(15). Nevertheless, despite the BD2 selectivity, RVX2135 blocks cell-cycle progression and induces cell death in Myc-induced mouse lymphoma cells in vitro and in mice (Figs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RVX2135 belongs to a different scaffold, which has a higher selectivity for BD2 over BD1 of the BET proteins. This property is shared by RVX-208, a BET inhibitor with the same scaffold that is undergoing clinical trial for arteriosclerosis (13)(14)(15). Nevertheless, despite the BD2 selectivity, RVX2135 blocks cell-cycle progression and induces cell death in Myc-induced mouse lymphoma cells in vitro and in mice (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…RVX2135 is a novel small-molecule BET bromodomain inhibitor that is structurally unrelated to the benzodiazepine derivative compounds but is in the same chemical scaffold group as RVX-208 developed by Zenith Epigenetics Corp. (Fig. 1A) (13)(14)(15). In a fluorescence resonance energy transfer assay in vitro, RVX2135 and the prototype BET inhibitor JQ1 displaced all four BET family members from tetraacetylated histone peptide (Brd2, Brd3, Brd4, and BrdT) with low or submicromolar potency ( Fig.…”
Section: Rvx2135 Blocks Proliferation Of Myc-induced Mouse Lymphoma Cmentioning
confidence: 99%
“…To test if our definition of regulatory potential could predict BET-inhibitor repressed genes, we examined five diffuse large Bcell lymphoma (DLBCL) cell lines (Chapuy et al 2013), one liver cancer cell line (HepG2) (Picaud et al 2013) and one malignant peripheral nerve sheath tumor cell line (90-8TL) (De Raedt et al 2014) in which BET-inhibitor effects were measured using expression microarrays and H3K27ac ChIP-seq (Chapuy et al 2013;Picaud et al 2013;De Raedt et al 2014). Using H3K27ac ChIP- Figure 1.…”
Section: H3k27ac Defined Regulatory Potentials Identify Genes Suppresmentioning
confidence: 99%
“…Studies have shown that BD selective BETis modify different transcriptional outcomes compared with non-selective BETis (Picaud et al, 2013;Gacias et al, 2014), implying that BD selectivity may have differential biological consequences that impact inflammation. RVX-297 is a novel, orally bioavailable BETi that has a 47-to 58-fold greater affinity for BD2 than for BD1 in the BET family of proteins (Kharenko et al, 2016).…”
Section: Introductionmentioning
confidence: 99%